2009
DOI: 10.4103/0250-474x.57306
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous RP-HPLC and HPTLC estimation of fluoxetine hydrochloride and olanzapine in tablet dosage forms

Abstract: A binary mixture of fluoxetine HCl and olanzapine was determined by two different methods. The first method involved determination of fluoxetine HCl and olanzapine using reversed-phase liquid chromatography using acetonitrile:methanol:0.032 M ammonium acetate buffer (45:05:50, v/v/v) as the mobile phase at a flow rate of 1.5 ml/min. Quantitation was achieved with ultraviolet detection at 235 nm over concentration ranges of 0.2-4 and 0.1-2 μg/ml; mean accuracies were 101.16±0.59 and 99.79±0.56% for fluoxetine H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…Os resultados do ensaio de exatidão, realizado em três níveis de concentração e em triplicata, utilizando comprimidos manipulados (Tabela 4), revelaram que todos os métodos apresentam recuperações dentro da faixa estabelecida pela ANVISA (80-120%), 21 no entanto, o melhor método para análise do cloridrato de fluoxetina é o 2D (239,5 nm) pelo ratio spectra, onde as recuperações variaram entre 99 a 103%, e para olanzapina é o método 3D (318,5 nm) com recuperações na faixa entre 99 a 100%, sendo comparáveis aos resultados obtidos por outros autores 4,17,18 que utilizaram a técnica de cromatografia líquida de alta eficiência.…”
Section: Exatidãounclassified
See 1 more Smart Citation
“…Os resultados do ensaio de exatidão, realizado em três níveis de concentração e em triplicata, utilizando comprimidos manipulados (Tabela 4), revelaram que todos os métodos apresentam recuperações dentro da faixa estabelecida pela ANVISA (80-120%), 21 no entanto, o melhor método para análise do cloridrato de fluoxetina é o 2D (239,5 nm) pelo ratio spectra, onde as recuperações variaram entre 99 a 103%, e para olanzapina é o método 3D (318,5 nm) com recuperações na faixa entre 99 a 100%, sendo comparáveis aos resultados obtidos por outros autores 4,17,18 que utilizaram a técnica de cromatografia líquida de alta eficiência.…”
Section: Exatidãounclassified
“…12 Para análise do cloridrato de fluoxetina há vários trabalhos que apresentam métodos usando espectrofotometria nas regiões do UV 1 e visível com formação de complexos, 13,14 técnicas eletroquímicas, 15 turbidimétricas 16 e cromatografia líquida de alta eficiência (CLAE) para sua determinação em medicamentos, sendo esta última a técnica oficial apresentada nas Farmacopeias Americana e Brasileira. 1 Para análise dos fármacos em formulações farmacêuticas contendo a combinação olanzapina e cloridrato de fluoxetina a técnica empregada é CLAE, 4,17,18 que apresenta alguns inconvenientes como o uso de equipamentos caros e procedimentos complexos, o que torna o método pouco acessível e, em alguns casos, inviáveis.…”
Section: Introductionunclassified
“…The literature survey revealed spectroscopic [5][6][7][8][9][10][11][12] and chromatographic [13][14][15][16][17][18] methods.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…A survey of literature revealed that spectrophotometric 3,4 , spectrofluorimetric 5,6 , electrochemical 7 , gas chromatography 8 , liquid chromatography [9][10][11] , capillary zone electrophoresis (CZE) 12 methods for determination of FH from pharmaceutical formulation and spectrophotometric [13][14][15][16][17] , linear voltametric 16 , HPLC [16][17][18] , CZE 18 methods for determination of OZ from pharmaceutical dosage form whereas HPLC [19][20][21][22] and HPTLC 21,22 methods for the simultaneous determination of FH and OZ from combined dosage forms were reported.…”
Section: Fig 1b: Olanzapine Figure 1a and B: Chemical Structures Of Flmentioning
confidence: 99%